(untitled) (Journal of Science, Technology and Innovation Policy, 2021)
Malaysia’s economic transformation towards the status of a high income nation has led to the widespread demand for an accelerated corporatization policy; one where public sector agencies are transformed into business entities to facilitate the creation of knowledge and wealth. This shift was encouraged by successful corporatization models abroad, including those adopted by the Fraunhofer-Gesellschaft in Germany; the Korea Institute of Science and Technology (KIST) in Korea; and the National Institute of Standards and Technology (NIST) in the United States. These institutions have since encouraged a similar corporatization process in emerging and third world nations. However, corporatization comes along with a unique set of institutional challenges. This study aims to investigate the corporatization processes undertaken by various government research and technology organizations (GR&TOs) in Malaysia, and then to evaluate their overall progress. The outcome of this study indicates that a myriad of challenges can be inverted into growth opportunities through the application of appropriate strategic planning.